Effect of yoga exercise on metabolic and homeostatic parameters of insulin resistance - Pastucha, Dalibor; Filipčíková, Radka; Čajka, Vít; Horáková, Dagmar; Radová, Lenka; Reich, Petr; Sovová, Eliška (Acta medica martiniana, 2012)
The aim of this study is to assess the effect of yoga exercise on the anthropometric parameters and metabolic parameters in individuals regularly exercising yoga as well as to assess the possible impact on cardiovascular risk prevention. The study sample composed of two groups: A (57 healthy control) and B (61 subjects exercised yoga). For each group were measured: blood pressure, body mass index (BMI) and laboratory values of total cholesterol, triglycerides, high density lipoproteins (HDL) and low density lipoproteins (LDL) cholesterol, glycaemia and insulinemia, homeostasis model assessment of insulin resistance (HOMA-IR) and quantitative insulin-sensitivity check index (QUICKI). BMI was significantly lower (p= 0.005923) in the group B (yoga). We found an impact of yoga on the homeostatic indices HOMA-IR and QUICKI and it mens significantly lower value of systolic blood pressure (p= 0.043543) and LDL cholesterol levels (p=0.008714). Based on these outcomes, we consider yoga to be a suitable physical activity to prevent cardiovascular diseases.
Keywords: Female; ženské pohlaví; lidé; Blood Glucose; Sensitivity and Specificity; Exercise Therapy; senzitivita a specificita; jóga; Male; Cardiovascular Diseases; Insulin Resistance; inzulinová rezistence; kardiovaskulární nemoci; terapie cvičením; lidé středního věku; mužské pohlaví; Yoga; krevní glukóza; Middle Aged; Humans